Enhancing resilience: An interpretative phenomenological analysis of The Awe Project - Jeff Thompson (Journal of Community Safety and Well-Being, 2022)
Awe is a complex emotion often associated with experiencing multiple other positive emotions during a captivating and immersive experience. Engaging in awe experiences contributes to enhancing an individual’s personal resilience and wellbeing. Moreover, the benefits of experiencing awe transcend the individual, as it has been described as a self-transcendent emotion provoking concern beyond the self. Using an Interpretative Phenomenological Analysis (IPA) methodology, this exploratory paper evaluates the impact of The Awe Project, an online resilience and well-being program that can be accessed on mobile devices, on a specific cohort of participants. Data analysis consisted of examining participant post-program surveys and comments made during the program. Results indicate the program supported participants’ resilience and well-being through evoking awe and using other mindfulness and resilience practices, such as having a sense of agency, cognitive reappraisal, connectedness, controlled breathing, gratitude and appreciation, meaning and purpose in life, and optimism and prospection.